2013
DOI: 10.1007/s10992-013-9298-y
|View full text |Cite
|
Sign up to set email alerts
|

Action Emulation between Canonical Models

Abstract: In this paper we investigate Kripke models, used to model knowledge or belief in a static situation, and action models, used to model communicative actions that change this knowledge or belief. The appropriate notion for structural equivalence between modal structures such as Kripke models is bisimulation: Kripke models that are bisimilar are modally equivalent. We would like to find a structural relation that can play the same role for the action models that play a prominent role in information updating. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Following work by van Eijck et. al ( [31,19]) we propose a notion of 'equivalence' for program models. Our presentation is similar to the exposition of [27, Chapter 6, Section 6.1], here, we built on results presented there, and will focus in our proofs on the differences.…”
Section: When Are Two Programs the Same?mentioning
confidence: 99%
“…Following work by van Eijck et. al ( [31,19]) we propose a notion of 'equivalence' for program models. Our presentation is similar to the exposition of [27, Chapter 6, Section 6.1], here, we built on results presented there, and will focus in our proofs on the differences.…”
Section: When Are Two Programs the Same?mentioning
confidence: 99%
“…We say that two action models A 1 and A 2 are equivalent, written A 1 ≡ A 2 , if for any epistemic model M, M ⊗ A 1 ↔ M ⊗ A 2 , where ↔ denotes standard bisimulation on epistemic models [17].…”
Section: Definition 3 (Product Update)mentioning
confidence: 99%
“…In [24] a notion of parametrized action emulation is defined that characterizes action model equivalence. In [62,63] this is replaced by a nonparametrized action emulation relation, and it is shown that this characterizes action model equivalence for canonical action models (action models with maximal consistent subsets of an appropriate closure language as preconditions). The question whether non-parametrized action emulation also characterizes action model equivalence for arbitrary action models is still open.…”
Section: Further Connectionsmentioning
confidence: 99%